Incorporation of betacyanin-rich extracts in ice cream: comparison among different additives and control formulation - Roriz, Custódio Lobo (2017)
Food appearance is as important as its taste. Colour preservation, for instance, is one of the top concerns throughout food processing [1] . Nowadays, the main trend is developing visually appealing foods, which simultaneously should contain enhanced functional properties. Products typically containing limited levels of bioactive compounds, such as the widely consumed ice cream, present better possibilities for improvement [2]. Ice creams are complex colloidal systems combining milk, sweeteners, emulsifiers, stabilizers, colouring and flavouring agents. These ingredients are often artificial, but they could be replaced by natural alternatives, fulfilling the current concern about cleaner labels. Colouring agents, in particular, are highly valued by consumers, who prefer natural compounds instead artificial ones, often perceived as being harmful [3]. In fact, some natural dyes are already available on the market, but other alternative sources could be exploited. Betalains, which can be divided in red-violet betacyanins and yellow-orange betaxanthins are a good example of compounds deserving higher attention. Betacyanins are usually derived from beetroot, but they can be obtained from different sources such as the purple flowers of Gomphrena g/abosa L. (Amaranthaceae) [4]. Accordingly, betacyanins from G. globosa were used as colouring agents in ice creams and further compared with other ice cream formulations (containing commercial betalain or free of any colouring agents). Besides the colouring strength, the nutritional parameters, individual sugars and fatty acids profiles were also compared. To obtain a thorough characterization, all parameters were evaluated in five different times: preparation day and after 15, 30, 45 and 60 days of storage. Nutritional parameters, except protein along storage time (ST) and ash among ice cream formulations (IF) showed significant differences either comparing different ST or IF. Nevertheless, while colour parameters remained unchanged along ST (except L * in fresh samples), they varied significantly in each IF. On the other hand, ST proved to be a stronger effector on fatty acids than IF, which caused no significant changes in most cases. Overall, both natural extracts proved to be suitable alternatives to the commercial dye (betalain), according to the maintenance of nutritional and fatty acids profiles and improvement in the appearance of the tested food product.